Mechanisms of Professional Competence Improvement by Preparing Future Physical Education Teachers for Innovative Activity - Botirjon qizi, Karimova Gulhayo (European Journal of Life Safety and Stability (2660-9630), 2022)
Nowadays, it can be seen from the world experience that new, modern teaching methods and tools are rapidly entering the educational process and they are being used effectively. In our country, the system of effective use of modern technologies in the educational system is aimed at making students become experienced specialists and devotees of their profession in the future. This article provides information about the mechanisms of improving professional potential by preparing future physical education teachers for innovative activities.